1998
DOI: 10.1128/aem.64.7.2554-2559.1998
|View full text |Cite
|
Sign up to set email alerts
|

Use of Green Fluorescent Protein To Tag and Investigate Gene Expression in Marine Bacteria

Abstract: Two broad-host-range vectors previously constructed for use in soil bacteria (A. G. Matthysse, S. Stretton, C. Dandie, N. C. McClure, and A. E. Goodman, FEMS Microbiol. Lett. 145:87–94, 1996) were assessed by epifluorescence microscopy for use in tagging three marine bacterial species. Expression of gfp could be visualized in Vibrio sp. strain S141 cells at uniform levels of intensity from either the lac or thenpt-2 promoter, whereas expression of gfp could be visualized in Psychrobacter sp. strain SW5H cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 46 publications
(52 reference statements)
0
37
0
Order By: Relevance
“…Green fluorescent protein (GFP)‐expressing strains are now frequently used for tracking specific microbial strains in ecosystems. Bacteria marked with gfp have been employed to study the distribution and dynamics of bacterial populations in soils (Errampalli et al ., 1998; Tresse et al ., 1998), aqueous systems (Stretton et al ., 1998), rhizospheres (Gage et al ., 1996; Bloemberg et al ., 1997; Tombolini et al ., 1997), activated‐sludge (Eberl et al ., 1997; Olofsson et al ., 1998) and biofilms (Möller et al ., 1998; Skillman et al ., 1998). Furthermore, GFPs can be used to visualize gene expression (Cubitt et al ., 1995; Andersen et al ., 1998; Jaspers et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Green fluorescent protein (GFP)‐expressing strains are now frequently used for tracking specific microbial strains in ecosystems. Bacteria marked with gfp have been employed to study the distribution and dynamics of bacterial populations in soils (Errampalli et al ., 1998; Tresse et al ., 1998), aqueous systems (Stretton et al ., 1998), rhizospheres (Gage et al ., 1996; Bloemberg et al ., 1997; Tombolini et al ., 1997), activated‐sludge (Eberl et al ., 1997; Olofsson et al ., 1998) and biofilms (Möller et al ., 1998; Skillman et al ., 1998). Furthermore, GFPs can be used to visualize gene expression (Cubitt et al ., 1995; Andersen et al ., 1998; Jaspers et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, K. ascorbata SUD165/26 was labeled with green £uorescent protein (GFP) from the jelly¢sh Aquoria victoria, and with luciferase (Lux) from the bacterium Vibrio harveyi. GFP and Lux are both very sensitive, easily detected and can be quanti¢ed with a spectro£uorimeter or a luminometer [13,14], thereby providing a simple and accurate means of monitoring and localizing selected bacteria in a complex environment.…”
Section: Introductionmentioning
confidence: 99%
“…10% of the cells had lost the plasmid (data not shown). Other studies using bacteria tagged with a plasmidbased gfp construct also demonstrated that during colonization of substrates, part of the population lost their ability to express GFP (Gage et al 1996;Stretton et al 1998). To guarantee stable expression in long term in planta studies, the gene encoding GFP should be introduced into the bacterial chromosome, which is more stable than those plasmidborne (Errampalli et al 1999).…”
Section: Discussionmentioning
confidence: 99%